HUBUNGAN KONSUMSI MINUMAN MANIS DAN AKTIVITAS FISIK DENGAN STATUS INDEKS MASSA TUBUH PADA REMAJA DI KOTA MEDAN - health, Amelia; Najla Rifda Syahfitri; Mami Azzahra Lubis; Epidemiologi, Cut Mulyana Moely; Wahyudi (SEKOLAH TINGGI ILMU KESEHATAN INDRAMAYU, 2025)
Adolescents' nutritional status is impacted by changes in their lifestyle in metropolitan regions, such as a greater intake of sugary drinks and less physical exercise. The purpose of this study was to examine the relationship between the body mass index (BMI) of adolescents in Medan City and their consumption of sugary drinks and physical activity. 200 female undergraduate students who were chosen via incidental sampling were the subjects of the quantitative, cross-sectional study. An online survey couducted to collect the data, and Spearman's rho and chi-square tests were used for analysis. The results of curren study show that, the majority of respondents was in moderate physical activity (94.5%) and consumed few sugar-filled beverages (65.7%). The nutritional status of 59.2% of respondents was considered normal. Consumption of sugar-filled beverages and physical exercise were significantly correlated with nutritional status (p = 0.001). These results highlight the value of physical activity promotion and nutrition education in preventing nutritional issues in teenagers.